Writing a Literature Review Narrative - Barbara R. Schirmer (International Journal of Education, 2024)
The purpose of this paper is to present an approach for translating the copious background material gathered from the professional literature into a coherent and compelling written document. The approach includes steps for weaving together summary information from each study in a way that offers the reader a logical and clear description of pertinent methodological and conceptual issues and the implications for further research. The step-by-step approach enables both the novice and veteran researcher to translate the details of each study into a cogent synthesis that leads to determining the base of knowledge about the topic.